Glass transition of anhydrous starch by fast scanning calorimetry. (1st October 2017) - Monnier, Xavier; Maigret, Jean-Eudes; Lourdin, Denis; Saiter, Allisson
Highlights: The glass transition of anhydrous starch can be measured by Fast Scanning Calorimetry. The value measured at 312 °C is in agreement with extrapolated value of 316 °C. Structural relaxation of anhydrous starch can be observed by Fast Scanning Calorimetry. Abstract: By means of fast scanning calorimetry, the glass transition of anhydrous amorphous starch has been measured. With a scanning rate of 2000 K s −1, thermal degradation of starch prior to the glass transition has been inhibited. To certify the glass transition measurement, structural relaxation of the glassy state has been investigated through physical aging as well as the concept of limiting fictive temperature. In both cases, characteristic enthalpy recovery peaks related to the structural relaxation of the glass have been observed. Thermal lag corrections based on the comparison of glass transition temperatures measured by means of differential and fast scanning calorimetry have been proposed. The complementary investigations give an anhydrous amorphous starch glass transition temperature of 312 ± 7 °C. This estimation correlates with previous extrapolation performed on hydrated starches.